UFIDA (F) - McFarlan, F. Warren (Franklin Warren); Li, Donghong; Guo, Jia ([London] : SAGE, 2016)
In January 2010, UFIDA started its new three-year development plan. The goal was clear: scale revenue to become a World Top 10 management software and service provider and gain number one position in the e-business service market in China. Financing was seen an essential tool to achieve these goals. This text outlines the strategies employed by UFIDA to achieve these goals.
Originally Published in: Liu, L., McFarlan, F. W., & Li, D. (2012). UFIDA (F). 3-811-371. Beijing: Tsinghua SEM China Business Case Center.
Description based on online resource; title from home page (viewed on April 28, 2016).
Keywords: elektronické knihy; electronic books; UFIDA (Firm); Organizational change -- Case studies; Strategic planning -- Case studies